Hot extrusion followed by a hot ecap consolidation combined technique in the production of Boron Carbide (B4C) reinforced with aluminium chips (AA6061) composite - Al-Alimi, Sami; Lajis, Mohd Amri; Shamsudin, Shazarel; Yusuf, Nur Kamilah; Chan, B. L.; Hissein, Didane Djamal; H. Rady, Mohammed; Msebawi, Muntadher Sabah; Sabbar, Huda Mohammed (2021)
A new and promising MMC approach to the reduction of pollution, greenhouse effects, and emissions is to develop a technology related to materials composite forming. Hot extrusion followed by hot ECAP is a combination of solid-state recycling method (direct recycling) that consists of chip preparations, cold compaction, and hot extrusion, followed by the ECAP process. The developed process is used to consolidate the chips for direct chip recycling purposes without the remelting phase. In this study, finished or semi-finished products from B4C-reinforced particles and AA6061 aluminium chips were produced. The samples made by hot extrusion were compared with samples obtained from hot extrusion followed by the hot ECAP process in terms of mechanical properties. Additional plastic deformation by hot ECAP after hot extrusion significantly increased the mechanical properties of the MMC compared with the samples obtained from the hot extrusion only. The density and microstructure of the samples were also determined.